EBSD-assisted fractographic analysis of crack paths in magnesium alloy (Fracture and Structural Integrity, 2015)
Magnesium (Mg) alloys are attractive as structural materials due to their light weight and high specific strength. It is well known that Mg alloy has hexagonal close-packed (HCP) structure and only basal slipor twinning can operate during plastic deformation because critical resolved shear stresses of the other slipsystems such as pyramidal or prismatic slips are much higher than the basal slip. Thus sometimes characteristicfracture surfaces are formed during stress corrosion cracking (SCC) or fatigue crack propagation (FCP) in Mgalloys, where many parallel lines are formed. These lines are different from so-called fatigue striations, becausethey are formed even under sustained load condition of SCC. Consequently, electron back scattered diffraction(EBSD) technique was applied on the fracture surface, and the formation mechanism of parallel lines wasinvestigated. EBSD-assisted fractography had revealed that the characteristic parallel lines were formed due tothe operation of basal slips, not twining. It is considered that hydrogen-enhanced localized plasticity (HELP)mechanism had been activated under corrosive environment.
Keywords: EBSD-assisted fractography